2011
DOI: 10.1007/s10853-011-6121-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of IF steel deformed during plane stress local torsion

Abstract: A novel localized severe plastic deformation process for reinforcement of fastener holes is presented.This process is capable of inducing large shearing strains confined to an axi-symmetric zone around a hole. The process was applied to thin interstitial free steel samples. In the material around the hole, significant grain refinement was achieved, and a gradient of refinement was observed moving away from the hole. The ultimate and yield strengths were increased by 28% and 100% respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The implementation method is explained in detail elsewhere. 22 During the local torsion process, the history of torque which is needed to twist the specimen through a specified twist angle can be recorded during experiments and the numerical simulation as well. In order to make sure that the results of the finite element simulations for the local torsion are reliable, the numerical and experimental torque-twist curves were compared as illustrated in Fig.…”
Section: Analysis Of Local Torsionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation method is explained in detail elsewhere. 22 During the local torsion process, the history of torque which is needed to twist the specimen through a specified twist angle can be recorded during experiments and the numerical simulation as well. In order to make sure that the results of the finite element simulations for the local torsion are reliable, the numerical and experimental torque-twist curves were compared as illustrated in Fig.…”
Section: Analysis Of Local Torsionmentioning
confidence: 99%
“…Although this is not the case with the local torsion process, however the advantages of grain refinement from the local torsion in improving the mechanical strength of the material around the hole surface has already been established. 22 The usefulness of the local torsion with or without the cold expansion cannot be solely assessed based on its capability in producing compressive residual stresses. The investigation has to include the interaction of grain refinement and the residual stress on the overall performance of a fastener hole subjected to the CELT.…”
Section: Residual Stress On Mid-thickness Planementioning
confidence: 99%
“…However, the UFG microstructure brought about limited ductility with a few percent uniform elongation that limits its applications ( Ref 23). Previous reports have shown that the ductility of UFG materials can be enhanced without compromising the strength by appropriate annealing treatments after SPD (Ref [22][23][24][25].This improvement was attributed to the bimodal grain size distribution introduced into the deformed microstructure with the combination of fine and coarse grains (Ref [25][26][27][28][29]. Review of UFG low carbon steel suggests that both high strength and ductility can be achieved by combining a few percentage of micron-sized (1-10 lm) grains in UFG matrix (Ref 4).…”
Section: Introductionmentioning
confidence: 98%
“…Nowadays, SPD is highly desirable for the application and increasingly introduces pure shear and simple shear in the deformation process . Conventional SPD methods, such as equal channel angular press (ECAP) and twist extrusion (TE), have been introduced to achieve the local grain refinement or bulk grain refinement to strengthen the materials. However, they have a relatively high requirement for the deformation dye and equipment, especially for the high yield strength materials to realize SPD difficultly, such as steel, whose yield strength is almost 1300 MPa.…”
Section: Introductionmentioning
confidence: 99%